The musical-creative and pedagogical activity of Solomiya Krushelnytska: contribution to the development of Ukrainian music education - Valentyna V. Bielikova (Academy of Cognitive and Natural Sciences, 2024)
This article examines the musical-creative and pedagogical activity of the prominent Ukrainian opera singer Solomiya Krushelnytska (1872-1952) and her contribution to developing Ukrainian music education in the first half of the 20th century. Utilising theoretical approaches to studying personality within the cultural-historical context, we explore Krushelnytska's life path as an example of combining artistic activity and pedagogical practice. The research analyses biographical materials, students' memoirs, and critical reviews of the singer's performances. The results show that Krushelnytska significantly contributed to popularising Ukrainian vocal art internationally and played an essential role in developing vocal pedagogy in Ukraine. Her pedagogical principles, grounded in her personal experience and methods of the Italian vocal school, promoted the formation of new generations of Ukrainian opera performers.